2019
DOI: 10.1155/2019/5787206
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the Masquerader: A Delayed Diagnosis of MS and Its 4.5 Years of Implications in an Older African American Male

Abstract: Multiple sclerosis (MS) has classically been described as a disease of the young Caucasian female. While the prevalence may seem to be higher in Caucasians (CAs), recent studies suggest that the real incidence of MS may actually be higher in African Americans (AAs). Here, we discuss a nonclassical case of MS in an older African American male, prognostic factors, disease patterns in African Americans, and how a delay in diagnosis and socioeconomic factors can lead to worse outcomes. In patients that present wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
2
1
2
Order By: Relevance
“…Several studies have shown that African Americans have significantly higher CNS lesion burden, more frequent relapses, worse ambulatory disability, worse post-relapse recoveries, and higher overall disability at diagnosis [5,10,19,29]. Overall, our findings did not confirm these prior observations and we believe that the similar socioeconomic background of this patient cohort, along with the small sample size, may have contributed to this.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Several studies have shown that African Americans have significantly higher CNS lesion burden, more frequent relapses, worse ambulatory disability, worse post-relapse recoveries, and higher overall disability at diagnosis [5,10,19,29]. Overall, our findings did not confirm these prior observations and we believe that the similar socioeconomic background of this patient cohort, along with the small sample size, may have contributed to this.…”
Section: Discussioncontrasting
confidence: 94%
“…Consistent with published reports, a greater proportion of NH-Black patients had early severe disability (defined in our study as an estimated EDSS score > 4.5) when compared to NH-White and Hispanic patients [29,30]. In our present study, treatment modality did not impact the risk of having an estimated EDSS score > 4.5 at the last visit.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with published reports, NH-Black patients had a higher risk for early severe disability (defined in our study as an estimated EDSS > 4.5) when compared to NH-White and Hispanic patients [30,31]. In our present study, treatment modality did not impact the risk of having an estimated EDSS > 4.5 score at the last visit.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that African Americans have significantly higher CNS lesion burden, more frequent relapses, worse ambulatory disability, worse postrelapse recoveries, and higher overall disability at diagnosis [5,10,20,30]. Although there appeared to be an increase in the degree of atrophy and MRI involvement in NH-Black compared to other groups, the trend observed in our study was not significant.…”
Section: Discussioncontrasting
confidence: 82%
“…Many participants felt that providers were reluctant to consider MS as a diagnosis because they were African-American, and several admitted that they were also surprised that Blacks could have MS. Their experience with delays in diagnosis is consistent with Dong, et al's report of delayed diagnosis leading to worse outcomes for African Americans. 20 In addition, given the presumed rarity of MS in African-Americans, our participants tended to encounter skepticism and lack of awareness and understanding from friends and families who knew little about MS and found it hard to believe that a Black person could have it.…”
Section: Discussionmentioning
confidence: 98%